The functional and cosmetic outcome of the ventral slit procedure for congenital megaprepuce - Tasker, David Beaumont (Division of General Surgery, 2022)
Background: Congenital Megaprepuce is a urological condition characterized by a megapreputial reservoir with a long redundant inner prepuce. The condition has been linked to urinary tract infections, lower urinary tract symptoms, and ballooning of the penis during voiding. An impeded urinary stream and resultant ballooning is associated with discomfort and causes parental anxiety due to the unusual appearance of phallus. Surgical correction should improve functionality, but cosmesis is also important. This study took place in a community in which traditional circumcision remains an essential rite of passage. Therefore, early surgical correction of congenital megaprepuce was complicated by the unique requirement that patients remain uncircumcised. Methodology: Here we investigated the functional and cosmetic outcomes of the ventral slit procedure, an uncomplicated technique used to restore urinary flow which, importantly, preserves the foreskin. Parents of 18 paediatric patients were interviewed post-operatively regarding phallic appearance and functionality following surgery. Results: Overall, the ventral slit procedure successfully restored flow, prevented ballooning and alleviated discomfort during voiding in all patients. Parents interviewed were highly satisfied with surgical outcomes, as assessed by the Pediatric Penile Perception score. Conclusion: The ventral slit procedure was found to be a culturally acceptable and simple surgical solution to congenital megaprepuce.